Assessment of Factors and Level of Patient Satisfaction in Out-patient Department of a Private Hospital (KYAMC Journal, 2024)
Background: Measurement of patient satisfaction in the outpatient department (OPD) of a hospital can be used to evaluate and redesign the process of caregiving and to improve the quality of services. Sometimes study findings depend on the setting.Objectives: a) To identify the factors associated with the patient's experience, and satisfaction about health care services of Out-patient department(OPD) of Khwaja Yunus Ali Medical College Hospital receives multidisciplinary health services. b) To measure the satisfaction level regarding doctors, health assistance, and other auxiliary staff working in OPD to help patients.Materials and Methods: A cross-sectional study was conducted among 914 patients of age ranging from 1 to 80 years selected randomly from OPD between January 2021 and May 2021. A self-designed semi-structured questionnaire was developed to assess patients' satisfaction with health care services. Statistical analysis was done by online computer software.Results: Overall 92.23 % of the patients were satisfied with the behaviour of the doctors and 75.93 % were satisfied with the services of other staff, and the remaining 7.77% were unsatisfied with doctors' behaviour and 24 % with other staff services respectively.Conclusions: The percentages of unsatisfied patients were deficient. Various deficiencies should always be covered by the hospital administration that will turn into a good result of improvement in the hospital services for more satisfaction of the patients.KYAMC Journal Volume: 14, No: 04, January 2024: 234-239.